(untitled) (Research, Society and Development, 2023)
Ethnography has its roots in anthropology, in which it consists of describing the way of life of a people or a group of people. The ethnographic studies in the educational area that tried to describe in detail the representations of the social actors and the activities developed in the school routine. An investigation with an ethnographic approach cannot be restricted to occasional encounters, but needs to interact, find a harmony between the available time and the researched context. The article aims to demonstrate the importance of the ethnographic approach as a research method in educational sciences and its knowledge construction process. The act of investigating is preceded by the natural curiosity of the human being. We highlight 03 collection devices consistent with the ethnographic method, namely: documentary research, participant observation and ethnographic interview. The methodology was based on a literature review, in which the objective was to collect knowledge focused on the topic, as well as updated information. We have authors such as Lapassade, Gil, Fino, André, Yin among others, who collaborated with their studies for the development of the article, not only with the empirical dialogue, but also in a theoretical and dissertation way.